Dual Benzophenone/Copper‐Photocatalyzed Giese‐Type Alkylation of C(sp3)−H Bonds. Issue 70 (18th November 2019) - Abadie, Baptiste; Jardel, Damien; Pozzi, Gianluca; Toullec, Patrick; Vincent, Jean‐Marc
Abstract: Photocatalyzed Giese‐type alkylations of C(sp 3 )−H bonds are very attractive reactions in the context of atom‐economy in C−C bond formation. The main limitation of such reactions is that when using highly polymerizable olefin acceptors, such as unsubstituted acrylates, acrylonitrile, or methyl vinyl ketone, radical polymerization often becomes the dominant or exclusive reaction pathway. Herein, we report that the polymerization of such olefins is strongly limited or suppressed when combining the photocatalytic activity of benzophenone (BP) with a catalytic amount of Cu(OAc)2 . Under mild and operationally simple conditions, the Giese adducts resulting from the C(sp 3 )−H functionalization of amines, alcohols, ethers, and cycloalkanes could be synthesized. Preliminary mechanistic studies have revealed that the reaction does not proceed through a radical chain, but through a dual BP/Cu photocatalytic process, in which both Cu II and low‐valent Cu I/0 species, generated in situ by reduction by the BP ketyl radical, may react with α‐keto or α‐cyano intermediate radicals, thus preventing polymerization. Abstract : Radical copper : The presence of 2 mol % Cu(OAc)2 strongly inhibits the polymerization of highly polymerizable unsubstituted olefins engaged in benzophenone‐photocatalyzed radical Giese‐type alkylations of C(sp 3 )−H bonds (see scheme).